Diagnostic Utility of Beta-Catenin in Poorly Differentiated Colorectal Carcinoma - Farukh Mir Muhammad; Farhan Akhtar; Nighat Jamal; Rabia Ahmed; Muhammad Asif; Fatima Wahan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic ability of Beta-catenin in poorly differentiated colorectal carcinomas.Study Design: Cross-sectional studyPlace and Duration of Study: Department of Histopathology PNS Shifa Hospital, Karachi Pakistan from Jun 2019 to Jun 2020Methodology: After ethical approval from the Institutional Review Board, 60 patients of both gender and all age group, diagnosed with a case of colorectal carcinoma on biopsy and resection specimens analyzed on histopathology on H & E staining at PNS SHIFA were included in the study. The resection specimens of CRC included those obtained from hemicolectomy, abdominoperineal resection and biopsies. Beta-catenin was interpreted using immunohistochemistry as cytoplasmic and nuclear staining with varying intensity. The scoring method was 0 as negative, 1+ as weakly positive, 2+ as moderate positive, and 3+ as strongly positive.Results: Among the 60 patients with resection specimens included from hemicolectomy, abdominoperineal resection and colorectal biopsies, strong nuclear positive results were observed in 30(50 %) patients, moderate nuclear positivity in 12 (20 %), weak nuclear positivity in 6(10 %) and positive cytoplasmic staining in 12(20 %) patients.Conclusion: Beta-catenin can be used successfully as a diagnostic utility in poorly differentiated colorectal carcinoma patients.